A Study On Evaluation Of Economic Losses Due To Mastitis In Bovine In Purvanchal Region Of U.P. - Singh, Dhananjay; Kumar , Sanjay (Indian Journal of Veterinary Sciences and Biotechnology, 2013)
The present study was carried out to analyze the morbidity rate as well as to evaluate economic losses due to Mastitis in bovine in Purvanchal Region of Uttar Pradesh. Overall morbidity rate in lactating bovine was 15.5% in the study area. The morbidity rate of mastitis were higher in cows (18%) than in buffaloes (12.3%).Among cows crossbred cows were more affected (28.5%) than nondescript cows (6.5%). Chi square test statistic ( 2) concluded significant difference (P<0.05) of morbidity rates in between nondescript cattle and crossbreed cattle. Total economic losses due to mastitis per lactation in nondescript cows, crossbred cows and buffaloes were Rs.868.34, Rs1314.10 and Rs.1272.36 respectively.